2008
DOI: 10.1007/s10311-007-0104-3
|View full text |Cite
|
Sign up to set email alerts
|

HCH residues in point-source contaminated samples of the Teltow Canal in Berlin, Germany

Abstract: Contaminated groundwater and a riverine sediment core heavily affected by the same industrial point source were analysed for hexachlorocyclohexanes (HCH) and its degradation products. A detailed quantification by GC/MS revealed contamination levels up to 730 lg/L and 396 ng/g in sum for the water and sediment samples, respectively. The isomer pattern differed significantly in both compartments. The ground water samples were depleted in c-HCH, whereas a significant loss of a-HCH was evident in the sediments as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…74,2010 MICROBIAL DEGRADATION OF HCH 59 the environment with lower HCH concentrations due either to dispersal from stockpiles or to the use of the insecticide. The majority of HCH waste has been discarded in the open or stored at various levels of containment near the production sites, although in some cases, the top layer of soil at such sites has been removed for use in filling material for the construction of roads and buildings (97,145,181). HCH residues at many of the sites have percolated into the soil and thence contaminated groundwater (145).…”
Section: Fig 2 Known Locations Of Hch Dumps In Excess Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…74,2010 MICROBIAL DEGRADATION OF HCH 59 the environment with lower HCH concentrations due either to dispersal from stockpiles or to the use of the insecticide. The majority of HCH waste has been discarded in the open or stored at various levels of containment near the production sites, although in some cases, the top layer of soil at such sites has been removed for use in filling material for the construction of roads and buildings (97,145,181). HCH residues at many of the sites have percolated into the soil and thence contaminated groundwater (145).…”
Section: Fig 2 Known Locations Of Hch Dumps In Excess Ofmentioning
confidence: 99%
“…The majority of HCH waste has been discarded in the open or stored at various levels of containment near the production sites, although in some cases, the top layer of soil at such sites has been removed for use in filling material for the construction of roads and buildings (97,145,181). HCH residues at many of the sites have percolated into the soil and thence contaminated groundwater (145). Residues of HCH isomers have now been reported for many countries in samples of air (76,79,138), water (8,71,139), soil (29,50,71,139,144), food commodities (7,17,175,184), milk (153,197), fish (44,87), and mammals (48) and even from human blood samples (15,169) and adipose tissue (14,73).…”
Section: Fig 2 Known Locations Of Hch Dumps In Excess Ofmentioning
confidence: 99%
“…50 lL at ambient temperature. Soil and sediment subsamples of 10 g were extracted by sequential ultrasonic agitation (according to Ricking and Schwarzbauer 2008) with 100 mL acetone and 100 mL nhexane. Each extraction step involved 15-min treatment by ultrasonication followed by a stirring period of 1 h and a second 15-min treatment by ultrasonication.…”
Section: Extraction and Fractionationmentioning
confidence: 99%
“…Numerous studies were performed on the occurrence of HCHs in various environmental compartments such as air (e.g., Karlsson et al 2000;Ding et al 2007), soil (e.g., Manz et al 2001;Schwartz et al 2006), sediment (e.g., Heim et al 2005;Ricking and Schwarzbauer 2008;Li et al 2011a), water (e.g., Heemken et al 2000), plants (e.g., Abhilash et al 2008) and animals (e.g., Marth et al 1997;Willett et al 1998). Most of these studies focused either on selected isomers or on reported cumulated concentrations of all HCH isomers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation